The role of Gfi1s/1b transcription factors in the molecular programming of vertebrate erythropoiesis - Alnassay, Farah (2024)
The transcriptional repressors Gfi1 and Gfi1b play numerous roles in haematopoiesis. In different contexts, they limit or endorse cell proliferation, control apoptosis, and influence cell fate decisions. Our laboratory recently showed that Gfi1/Gfi1b proteins can also control the speed of cellular differentiation. It all started by the identification of the gene-trap line qmc551 that expresses a Green Fluorescent Protein (GFP) reporter in primitive red blood cells (prRBCs) that develop in the embryonic trunk and enter the circulation on day 1 of embryogenesis. The transposon trapped the gfi1aa gene, which is one of the two paralogous gfi1 genes in zebrafish. The qmc551 allele expressed GFP instead of Gfi1aa under the control of the gfi1aa promoter, yet homozygous carriers were viable and fertile. In prRBCs, gfi1aa and gfi1b are co-expressed in an overlapping pattern. Morpholino-mediated knockdown of Gfi1b caused prRBC maturation defects only in qmc551hom embryos, demonstrating the functional redundancy of gfi1aa and gfi1b proteins in prRBCs. RNA-Seq analysis showed that early qmc551hom;gfi1bMO prRBCs displayed reduced late erythroid and elevated endothelial gene expression. Similar but milder changes were observed in gfi1aa single-mutant prRBCs. A series of whole-mount RNA in situ hybridisation experiments on single gfi1aa and double gfi1aa; gfi1b mutant embryos revealed that the differentiation of prRBCs was mildly delayed in gfi1aa single-mutants and substantially delayed in gfi1aa; gfi1b double-mutant embryos. The substantial delay was the cause of the previously observed maturation defect. Interestingly, these experiments also revealed upregulation of the second Gfi1 paralogue, Gfi1ab. New RNA-seq data on double mutant prRBCs using qmc554 line that carried the gfi1b mutant allele that was analysed in this project, besides highlighting morpholino-induced genes in the old data, confirmed the upregulation of gfi1ab. Using the newly generated gfi1ab mutant allele qmc553, we showed that triple mutant prRBCs had a much more dramatic phenotype. GFP+ prRBCs form in the trunk but struggle to enter circulation on day 1. By day 2, no prRBCs were observed in circulation. As TUNEL assays revealed apoptotic cells in the CHT region, we show that prRBCs undergone apoptosis by day 2 after the loss of all Gfi1s. Next, we studied the erythrocytes of kidney marrow (KM) cells to investigate previously reported abnormal differentiation of KM erythrocytes in gfi1b mutants. Flow cytometry analysis of KM cells on the qmc554 line carrying the gfi1b mutant allele with the gata1:dsRed reporter line revealed a massive reduction in red blood cells and an increase in progenitor population, suggesting that loss of gfi1b leads to maturation delay of red blood cells. Interestingly, the other gfi1b mutant line, sh339, had a mild reduction in number of gata1:dsRed cells, but the distribution of erythroid and progenitor cells was consistent with our qmc554 line. This suggests that the reduction in erythroid population and the overrepresentation of progenitor cell population are indeed due to the gfi1b mutation. To study the molecular changes in erythroid cells caused by the gfi1b mutation, single-cell RNA sequencing analysis was performed using qmc551hom;qmc554hom;gata1:dsRed/+ KM cells. Based on our previous studies on the qmc551 allele, gfi1aa is dispensable in definitive erythrocytes; therefore, using qmc551hom;qmc554hom;gata1:dsRed/+ would yield similar outcomes. Using the reporter line gata1:dsRed+, we were able to highlight erythroid and other gata1 expressing cells in KM. This analysis revealed a differentiation block in the erythroid population, which prevented erythroid proliferation. In addition, owing to misregulation in the molecular program, the thrombocyte population was expanded and probably stuck in the KM unable to leave and enter circulation, which explains the overrepresentation of progenitor cells over erythroid cells in the flow cytometry analysis.